Influence of lacto-fermented traditional and colored wheat grain wholemeal flour on wheat biscuit quality - Bartkiene, Elena (2024)
In this study, the non-treated and lacto-fermented (with Lacticaseibacillus paracasei LUHS244) wholemeal of new breed lines of colored wheat (blue 8558-1 and black 8472-5) and traditional wheat "Silva", was evaluated for the lactic acid bacteria (LAB) viable count, acidity, color parameters, amino acid (AA) profile, gamma-aminobutyric acid (GABA), and biogenic amine content. The addition of 50, 100, 150, 200, and 250 g of tested wheat wholemeal was used for biscuit preparation. The chromaticity characteristics of the dough and biscuits, dough pH, acrylamide concentration, overall acceptability, and volatile compounds (VC) were examined. In most cases, fermentation increased the AA and GABA contents in wheat wholemeal. The main biogenic amines in tested wholemeal were putrescine and spermidine. Wheat wholemeal, fermented for 48 h, was selected for biscuit preparation due to its lower pH and higher LAB viable counts. The acrylamide concentration showed correlations with individual VCs. In conclusion, wheat biscuits prepared with 200 and 250 g of non-fermented “Silva” wheat wholemeal, 50 and 100 g of non-fermented and fermented blue wheat wholemeal, as well as 50, 100, and 150 g of non-fermented black wheat wholemeal can be recommended for achieving appropriate acrylamide concentration reduction without impairing the sensory acceptability of the product.